Searching for the state and the market in American community development: reflections on editing Community Development in the Steel City (Concept: The Journal of Contemporary Community Education Practice Theory, 2013)
A reflection on the process of editing a publication with those involved in Community Development in Pttsberg USA. How the state and the market feature in practitioners analysis in explored.